A 19-day neonatal case with accidental alcohol intoxication during umbilical care (Annals of Medical Research, 2021)
Acute alcohol intoxication is a condition frequently defined in childhood, especially in adolescents, and is seen as extremely rare in infants. In this study, acute alcohol intoxication developed after accidentally spilling alcohol with 96% concentration to the face of a 19-day-old neonate during umbilical care is presented because it is a rare case in the neonatal period.
Keywords: Acute alcohol intoxication; ethanol; neonatal; skin antisepsis